Treatment of hepatocellular carcinoma with gluteus medius metastasis: a case report and a literature review - Li, Yanxin; Luo, Ji; Zhang, Jianyong; Sun, Mingqiang; Yang, Jinping (Frontiers in Oncology, 2025)
Hepatocellular carcinoma (HCC) accounts for 85%–90% of all primary liver cancers (PLCs). Owing to the occult nature of HCC, most patients present at an advanced stage at the time of initial diagnosis and have a poor prognosis. With regard to systemic therapy, targeted therapy and immunotherapy are currently the centers of clinical research. With regard to local treatment, surgical resection, radiofrequency ablation, hepatic artery chemoembolization, and radiotherapy are commonly used. Interstitial brachytherapy is commonly used for the treatment of cervical and genitourinary cancers. In this case, interstitial brachytherapy was used to treat gluteus medius muscle metastasis from PLC, with good local control and symptom relief.